ÙØ¹Ø§Ù„ÙŠØ© Ù†Ù…ÙˆØ°Ø¬ ØªØ®Ù…ÙŠÙ† Ø§Ù„ÙƒÙ„Ù…Ø© Ù„Ù†ØªØ§Ø¦Ø¬ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† ÙØµÙ„ Ø§Ù„Ù…ØªÙˆØ³Ø· Ù…Ø¬Ù„Ø³ ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø§Ø¬Ù†Ø¨ÙŠØ© Ø¨Ù…Ù†Ø·Ù‚Ø© Ø¯Ø§Ø± Ø§Ù„Ù„ØºØ© - Muhammad Bisrikhwan; iis mulaili (Institut Agama Islam Darusssalam Blokagung, 2021)
This research is motivated by the conditions of learning Arabic in Darul Lughoh Dormitory Foreign Language Development Institute, where student learning outcomes are still not optimal. Researchers try to solve these problems through the use of a cooperative model of guessing the word type to improve learning outcomes in Arabic for students. The formulation of the problems in this study are (1) How to apply the cooperative model of guessing words in Arabic subjects, the subject of the mufrodat subject of hobbies to improve Arabic learning outcomes for students in the Mutawassith class, the Institute for Foreign Language Development, Darul Lughoh Dormitory, Pondok Pesantren Darussalam Blokagung Banyuwangi in 2018 / 2019? (2) How to improve student learning outcomes through the use of the cooperative type guessing model in Arabic for students in the mutawassith class of the Foreign Language Development Institute of Darul Lughoh Boarding School, Darussalam Blokagung Banyuwangi Islamic Boarding School, 2018/2019 Academic Year. The results of the research on the application of the cooperative type guessing model in Arabic after going through the initial, core and final activity steps showed an increase in the learning outcomes of students in the Mutawassith class Foreign Language Development Institute Darul Lughoh boarding school Darussalam Blokagung Banyuwangi Academic Year 2018/2019 . Data from the first cycle shows the average value of student learning outcomes as a whole is 80 with a percentage of 63.63% completeness. Whereas in cycle II the average student learning outcomes became 90 with overall student learning completeness was 86.36%.